La aplicación de la acción de protección en la normativa constitucional ecuatoriana en el Juzgado Tercero de Garantías Civiles y Mercantiles del cantón Machala en el periodo 2012-2013. - Minuche Cuesta, Reyna Iliana (2015)
The current Constitution of the Republic brings a variety of substantial change to the Constitution of 1998 one of them, according to the new model of state governing in Ecuador, the constitutional state of law, is the implementation of the new protective action, legal guarantee of constitutional rights of the former surrogate protection. Indeed, the protective action, unlike the protection, appears as a process of knowledge, declarative, and no residual widely reparation. Being a new warranty on the Ecuadorian legal, highlights the differences and similarities between ancient protection and new protective action in order to contribute to the exercise and consolidation of this new legal guarantee thereafter finds once such differences shall be considered substantiated the need for regulation or boundary that safeguards this new guarantee to those vices that corrupted and denatured at protection in the past. Thus, the key role to be played by the legislature in the process of drafting the new Law of Guarantees and Constitutional Control, their work is reduced to using proportional and respectful legislative techniques with the constitutional provisions governing the action stands protection, otherwise, the product of its activity would become unconstitutional and prejudicial to the will of the constituent, who was no other than strengthen the guarantor, not limit it.